The Body as Fluid Dramaturgy: Live Art, Corporeality, and Perception - Di Benedetto, Stephen (Journal of Dramatic Theory and Criticism, 2002)
The Body as Fluid Dramaturgy: Live Art, Corporeality, and Perception